Association of Cholelithiasis after Diagnosis of Non-Alcoholic Chronic Liver Disease on Ultrasound - Zafar, Wajiha; Sheraz, Shayan; Kurd, Humna; Munawar, Mahnoor; Khan, Zahra; Fazal, Salman; Sarim, Muhammad; Abdullah, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Cholelithiasis is a common hepatobiliary disorder characterized by gallstone formation, frequently observed in patients with chronic liver disease (CLD). Hepatic dysfunction alters bile composition and motility, increasing the risk of gallstone development. The prevalence of gallstones among CLD patients varies across populations, necessitating further investigation. Objective: To determine the prevalence of cholelithiasis among patients with non-alcoholic CLD and assess its association with demographic factors such as age and gender. Methods: A cross-sectional study was conducted at the Radiology Department of WAPDA Hospital, Lahore over period of 6 months from April 2024 to August 2024, on 108 patients diagnosed with non-alcoholic CLD. Standardized ultrasound imaging was performed using a Toshiba AplioMx system with a 3–6 MHz transducer. The study population was selected through random sampling, and data were analyzed using IBM SPSS v25. Descriptive statistics, chi-square tests, and prevalence calculations were applied. A p-value ≤0.05 was considered statistically significant. Results: Among the 108 participants, 71 (65.7%) were male and 37 (34.3%) were female. Cholelithiasis was detected in 73 (67.6%) patients. Chi-square analysis showed no significant association between gender and gallstone presence (χ²=0.021, p=0.885). Conclusion: A high prevalence of cholelithiasis was observed in non-alcoholic CLD patients, emphasizing the need for routine hepatobiliary screening to prevent complications.